2022
DOI: 10.1002/oby.23411
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the effects of sucrose intake on the brain and white adipose tissue: Could autophagy be a possible link?

Abstract: Excess dietary sucrose is associated with obesity and metabolic diseases. This relationship is driven by the malfunction of several cell types and tissues critical for the regulation of energy balance, including hypothalamic neurons and white adipose tissue (WAT). However, the mechanisms behind these effects of dietary sucrose are still unclear and might be independent of increased adiposity. Accumulating evidence has indicated that dysregulation of autophagy, a fundamental process for maintenance of cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…Dysregulation of autophagy alters energy metabolism in hypothalamic neurons and white adipose tissue (WAT). Imbalance of autophagy in hypothalamic neurons can lead to increased caloric intake and weight gain, resulting in obesity and metabolic disorders ( 72 ). Mitochondrial autophagy is critical for protecting neurons in the hippocampal CA1 region from ischaemic stress injury ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of autophagy alters energy metabolism in hypothalamic neurons and white adipose tissue (WAT). Imbalance of autophagy in hypothalamic neurons can lead to increased caloric intake and weight gain, resulting in obesity and metabolic disorders ( 72 ). Mitochondrial autophagy is critical for protecting neurons in the hippocampal CA1 region from ischaemic stress injury ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we selected six effective lyophilization protectants: oligosaccharides, chitosan, maltose, mannitol, sorbitol, and L-lysine. Sucrose has been used as a lyophilized protective agent for many years, but in recent years it has been found that sucrose metabolizes to fructose and produces potential cardiovascular toxicity, so this option is ruled out in this study [ 22 ]. The ABC-NPs complex was used as a model for the nanocarriers, and the water molecules in the complex were purged using a freeze-drying technique.…”
Section: Introductionmentioning
confidence: 99%